What are the risks of transaminase and creatine kinase elevations with the use of a statin?. Issue 10 (October 2015) - Ranjan, Kumuda; Bhattacharyya, Adity
Abstract : Evidence‐Based Answer : Higher dose statins increase the risk of hepatic transaminase elevations, especially the hydrophilic statins (atorvastatin or pravastatin). Lipophilic statins (simvastatin or lovastatin) may increase the risk of creatine kinase elevation at higher doses (SOR: C, systematic review of RCTs using disease‐oriented outcomes).